Strategi Komunikasi Pengelola Perpustakaan Umum Kota Bogor Dalam Membangun Minat Baca Masyarakat - Putri, Meilia; Handayani, Prameswari; Puspanidra, Tiara (Media Bahasa, Sastra, dan Budaya Wahana, 2025)
The reading interest of the Indonesian people is still relatively low even though access to information is getting easier. The Bogor City Public Library is one of those that has succeeded in increasing the number of visitors through an effective communication strategy. This study aims to analyze the communication strategy of the management of the Bogor City Public Library in building the public's interest in reading and the obstacles to the communication strategy of the management of the Bogor City Public Library in building the public's interest in reading. The benefits of this research are expected to be a reference and provide new developments in the field of Communication Sciences, especially in the field of public relations. This research uses a qualitative research method with an exploratory approach. This research was carried out at the Bogor City Public Library. The results of the study show that in carrying out the communication strategy, the manager of the Bogor City Public Library uses planning stages which include determining sources, preparing messages, selecting media, identifying targets, and expected effects. Sociological barriers are the most influential obstacles because they are the main cause of the lack of initial public participation in literacy activities, so it will be difficult to go further in the process of building interest in reading. The conclusion is that the communication strategy used by the manager of the Bogor City Public Library in building people's interest in reading, the planning stage is the most effective because it is related to various aspects that will support the implementation of communication strategies, including the use of social media. However, its use still needs to be maximized in order to further build reading interest and encourage people to visit the library. There are seven obstacles experienced by the management of the Bogor City Public Library, namely physical, distance, psychological, sociological, anthropological, physiological, and semantic obstacles. Of the seven barriers, sociological barriers are the most influential. Keywords: communication strategy; library; reading interest